Direct Oral Anticoagulants in Atrial Fibrillation: Practical Considerations and Remaining Issues - Beyer-Westendorf, Jan (Hämostaseologie, 2021)
Preventing thromboembolic events, while minimizing bleeding risks, remains challenging when managing patients with atrial fibrillation. Despite large and successful trial programs, several clinical concerns remain which commonly relate to fears of over- or underexposure to drugs and unfavorable outcomes. After a short summary of the main phase III trial findings, this short review discusses the evidence and clinical relevance of common clinical concerns (correct direct oral anticoagulant [DOAC] dosing; DOAC in moderate-to-severe renal impairment; and the relevance of fasting, nasogastric tube feeding, or high body mass index) on DOAC plasma levels. Finally, the need for specific DOAC antidotes will be addressed.
Keywords: direct oral anticoagulants; atrial fibrillation; stroke